Pliocene to modern sediment routing in the Aare valley: implications for sediment recycling - Laura Stutenbecker; Matthias Hinderer; Jasper Berndt; Christoph Glotzbach; Fritz Schlunegger; Michael Schwenk (Swiss Journal of Geosciences)
Abstract Rivers transport sediment from source to sink, forming an essential part of sediment routing systems. Sediment generation is often assumed to be focused on the upstream reaches of mountainous rivers, characterized by high topographic gradients and high denudation rates. However, sediment recycling from uplifted and incised basin fills with relatively low topography, for example in foreland basins, may contribute significant amounts of material to the sediment cascade. Identifying and quantifying sediment recycling from such lowlands, however, is complicated by the lack of proxies sensitive to sediment recycling. Nevertheless, it is a crucial task in sedimentary system analysis, because any interpretation of allogenic or autogenic factors that control sediment dynamics in sedimentary systems strongly depends on where and how sediment is generated. We here present a sedimentary provenance study on the Aare river, a tributary to the Rhine river, which is sourced in the Swiss Alps and drains the Alpine foreland basin fill in its middle and lower reaches. Using garnet geochemistry as a proxy, the sediment sources in the Aare catchment can be precisely determined. We show that the modern Aare river carries garnet types incompatible with the crystalline rocks outcropping in the present-day catchment area, but compatible with Miocene sandstones of the foreland basin fill. By comparing modern-day fluvial sediment to Pleistocene and Pliocene paleo-Aare deposits we show that recycling from the foreland basin has been a dominant sediment generation process since the onset of the Pleistocene glaciation and the incision of river valleys. Instead, garnet compositions in a Pliocene terrace are more compatible with sediment sources in the Alpine crystalline core, pointing towards first-cycle sediment. Our study further emphasizes that (1) sediment recycling can be identified using appropriate provenance proxies, (2) provenance data are crucial to understanding the sediment dynamics and drainage evolution in Alpine river valleys, and (3) recycling from lowland basin fills may be a significant source of sediment that should be considered to prevent erroneous provenance interpretations.